Mapping the Intellectual Landscape of Islamic Modernity: A Bibliometric and Critical Discourse Analysis of Global Scholarship - Saputra, Kurniawan Dwi; Utomo, Agus Himmawan (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to explore the state of the art of Islamic modernity research using a VOSviewer bibliometric study. The research draws on the 5-year (2020-2025) SCOPUS database, utilizing the keyword